Efektifitas Pemberian Jus Jambu Biji Merah dan Konsumsi Sereal Terhadap Perubahan Kadar Hemoglobin pada Ibu hamil di Pustu Pojok Kota Kediri - Pradian, Galuh; Nikmah, Anis Nikmatul (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2018)
One way to increase hemoglobin degree of the pregnant woman is by consuming guava juice and cereal. Tomato and cereal contain vitamin C which faster the iron absorption, while cereal contains high iron and vitamin C which can fulfill the pregnant mothers need. The purpose of this research is to know the difference of effectiveness guava juice and cereal giving toward the degree of hemoglobin of pregnant woman. The sample is 26 which divide into 13 for guava juice and 13 for cereal consumption. The design research is used Quasy Experiment with Two groups pretest-posttest design approach by using t-test. The result shows that guava juice is more effective to increase hemoglobin degree for the pregnant woman in Puskesmas Sukorame, Kediri. It is hoped, this research will give benefit for pregnant woman as an alternative to increasing hemoglobin degree.Â Keywords: Pregnancy, Guava juice, Sereal, Hemoglobin